PELATIHAN DAN PENDAMPINGAN PENGELOLAAN KEUANGAN & PENJUALAN DALAM PENINGKATAN PENDAPATAN USAHA ORANG MUDA (Studi Kasus Pada Kec. Pringsewu dan Kec. Lampung Selatan) - Sussana Mery Purwati, Agnes; Kumagaya, Johanes; Bima Bayuwono, Vinsensius (Jurnal Abdimas Musi Charitas, 2022)
ABSTRACT The rapid development of technology in the current era requires every society to be able to keep up with changes related to these technological advances. These changes are increasingly felt at a time when the COVID-19 pandemic sweeps across the world. Especially in Indonesia, people have begun to adapt to changes during the pandemic outbreak, both in villages and in cities. All public access can be done using sophisticated communication tools and is always changing according to its development. The purpose of community service activities carried out for young people assisted by YPSK is to help increase income from sales businesses using social media and improve their ability to manage their finances. The young people assisted by LDA YPSK are young people who have an entrepreneurial spirit. They start from elementary, junior high, high school, and adults have been equipped with how to try to be entrepreneurship, especially with the Covid 19 pandemic outbreak not preventing them from continuing to try. The results of community service activities are that the participants can understand and apply their sales by using social media even though they live in the village but it does not make them to fail technology, they become aware of ways to increase sales through promotions on social media and by increasing their income will be able to manage their finances well so that they can predict the continuity of their business.